Staging, performing notations and communication - Lorente Bilbao, José Ignacio (Historia y Comunicación Social, 2014)
The performing notations are a wide range of textual practices being sparcely investigated both in the field of communication research, as in the field of performing arts. However, the staging directions, directing notebooks and notations in performing arts, are an important subject for research in communication and for the artistic research in general, as they keep memory of how the staging text has been constructed, as implicit theories and strategies that have guided the staging project.